Role of Leukotrienes and Leukotriene Modifiers in Asthma - Paolo Montuschi (MDPI AG, 2010)
Leukotrienes (LTs), including cysteinyl LTs (CysLTs) and LTB4, are potent lipid mediators that are pivotal in the pathophysiology of asthma phenotypes. At least two receptor subtypes for CysLTs - CysLT1 and CysLT2 - have been identified. Most of the pathophysiological effects of CysLTs in asthma, including increased airway smooth muscle activity, microvascular permeability and airway mucus secretion, are mediated by the activation of the CysLT1 receptor. LTB4 may have a role in the development of airway hyperresponsiveness, severe asthma and asthma exacerbations. Although generally less effective than inhaled glucocorticoids, CysLT1 receptor antagonists can be given orally as monotherapy in patients with persistent mild asthma. In patients with more severe asthma, CysLT1 receptor antagonists can be combined with inhaled glucocorticoids. This therapeutic strategy improves asthma control and enables the dose of inhaled glucocorticoids to be reduced, while maintaining similar efficacy. The identification of subgroups of patients with asthma who respond to CysLT1 receptor antagonists is relevant for asthma management, as the response to these drugs is variable. The potential anti-remodeling effect of CysLT1 receptor antagonists might be important for preventing or reversing airway structural changes in patients with asthma. This review discusses the role of LTs in asthma and the therapeutic implications of the pharmacological modulation of the LT pathway for asthma.